2016
DOI: 10.7740/kjcs.2016.61.1.064
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fatty Acid Composition in Peanut Seed by Near Infrared Reflectance Spectroscopy

Abstract: This study was conducted to develop a fast and efficient screening method to determine the quantity of fatty acid in peanut oil for high oleate breeding program. A total of 329 peanut samples were used in this study, 227 of which were considered in the calibration equation development and 102 were utilized for validation, using near infrared reflectance spectroscopy (NIRS). The NIRS equations for all the seven fatty acids had low standard error of calibration (SEC) values, while high R2 values of 0.983 and 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…NIRS has become a well‐accepted multitrait technology for quantitative analysis of different analytes in pharmaceutical and agro industries (Murphy, ). This technique has been successfully applied for breeding for altered fatty acid profile in soybean (Hurburgh, ; Sato & Kawano, ), sunflower (Vich, Velascob, & Martinez, ), almond (Cuesta, Fernández‐Martínez, Company, & Velasco, ), rapeseed‐mustard (Kim, Park, Choung, & Jang, ; Kumar, Chauhan, & Kumar, ), and peanut (Lee et al, ). Sundaram et al () suggested that reflectance derivative model is better than absorbance‐based model for the prediction of fatty acid profile in peanut seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NIRS has become a well‐accepted multitrait technology for quantitative analysis of different analytes in pharmaceutical and agro industries (Murphy, ). This technique has been successfully applied for breeding for altered fatty acid profile in soybean (Hurburgh, ; Sato & Kawano, ), sunflower (Vich, Velascob, & Martinez, ), almond (Cuesta, Fernández‐Martínez, Company, & Velasco, ), rapeseed‐mustard (Kim, Park, Choung, & Jang, ; Kumar, Chauhan, & Kumar, ), and peanut (Lee et al, ). Sundaram et al () suggested that reflectance derivative model is better than absorbance‐based model for the prediction of fatty acid profile in peanut seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Different quantitative predictive models are available for calibration development in NIRS (Rousel, Preys, Chauchard, & Lallemand, ). Of which, PLSR and its modification were used for calibration development for measurement of fatty acid profile and oil content in peanut seeds (Kavera & Hanchinal, ; Lee et al, ). In the present study, calibration model was developed through PLSR method, which represented the most relevant variations in oil, oleic acid, linoleic acid, and palmitic acid and established significant correlations between predictive value and actual value from GC (Tables and ).…”
Section: Discussionmentioning
confidence: 99%